GAMBARAN FAKTOR KEBERHASILAN KELURAHAN KRAMAS KOTA SEMARANG DALAM PROGRAM KAWASAN BEBAS JENTIK - Alfi Rizka Septianef; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2017)
Kramas village on November 2016 was declared as 100% toward wiggler free area because it met the factors of wiggler free area development. This study aims to description of Kramas village success factors in wiggler free area program.This study was descriptive research with quantitative method and cross sectional approach. By using simple random sampling technique, 91 housewives at Kramas village were selected as the sample. The data were collected from questionnaire and observation. The data were analyzed by using univariate analysis.The result of this study showed that respondents were in the age 26-35 years old (35,2%), graduated from college (34,1%) and work as a housewives (71,4%). Most of respondents had good knowledge about dengue hemorrhagic fever (DHF) disease (96,7%), suppportive attitude toward PSN (85,7%). Supervison by PJR RT team was good (76,9%), counseling about DHF disease by PJR RT team was good (76,4%), PKK regulation about PSN was good (69,%), support from the head of neighbourhood was good (72,5%), support from health workers was good (58,2%). Most of respondents had done good practice of PSN (79,1%).